Addressing Correctional Staff Stress through Interaction with Nature: A New Role for Occupational Therapy. (3rd July 2018) - Wagenfeld, Amy; Stevens, Julie; Toews, Barb; Jarzembowski, Sarah; Ladjahasan, Nora; Stewart, Jade; Raddatz, Chanel
ABSTRACT: Correctional staff are at risk for high levels of stress, and interaction with nature may buffer this stress. This descriptive study explored a relationship between interaction with nature and self-perception of stress for correctional system staff. Results showed that correctional staff experience stress and, in small numbers, use time outdoors to cope with that stress. The majority of correctional staff surveyed would like an outside decompression area at their institution, especially those who use outdoor time as a coping strategy and those who go outside during work breaks. The implications of these findings for occupational therapy are discussed.